Digital Watermarking for Recovering Attack Areas of Medical Images using Spiral Numbering - Syifak Izhar, Hisham; Afifah Nailah, Muhamad; Jasni, Mohamad Zain; Badshah, Gran; Nurul Wahidah, Arshad (IEEE, 2013)
Medical image is seen as one of crucial data that demand for authentication method in order to ensure that data has not been tampered. This paper has conducted a research proposing a recovery feature in an authentication watermark with spiral manner numbering, which shows a good numbering system of embedding. The schema is a fragile, blind watermarking. The operating time taken is short and the result is very promising with high PeakSignal-to-Noise-Ratio(PSNR)value and low Mean-Squared Error(MSE).